The analysis of turbulence and rotation U-3M torsatron plasma during transport barriers formation - Burchenko, P.Ya.; Kulaga, A.Ye.; Lozin, A.V.; Ocheretenko, V.L.; Pinos, I.B.; Pavlichenko, O.S.; Prokopenko, A.V.; Slavnyj, A.S.; Tarasov, M.I.; Tsybenko, S.A.; Skibenko, A.I. (Вопросы атомной науки и техники, 2006)
The analysis of plasma density oscillations and E×B rotation of U-3M torsatron plasma was performed by UHR correlation reflectometry during the transport barrier formation. The connections between these characteristics and the phenomenon of inner and edge transport barrier formation were determined experimentally at the different values of HF power and plasma density